Urban-rural gradient in biodiversity intactness across global cities - Naiyi Liu; Zihan Liu; Felista Kasyoka Kilunda; Yanqi Liu; Chao Qin (Ecological Informatics)
Identifying the urban-rural gradient in biodiversity variation is crucial to better understand the response of biodiversity dynamics to global urbanization. However, knowledge of this gradient in global cities remains limited, largely due to the constraints of ground-based experiments. In this study, through statistical analyses of global gridded 100 m Biodiversity Intactness Index (BII) data, we find that the global mean BII is 0.40 ± 0.07 and 0.60 ± 0.11 for the urban and rural areas, respectively. Significantly, this urban-rural BII difference was most pronounced in Africa and Asia. There is a notable and pervasive pattern of increasing BII along the urban-rural gradient in global cities. The global mean BII demonstrates an increase from 0.37 ± 0.07 in urban center to 0.63 ± 0.12 in the rural periphery. The difference in BII between the urban center and the rural periphery can reach 0.20 and 0.21 in Africa and Asia, respectively, representing 50 % and 54 % of the total BII in the urban centers. In addition, generalized additive models (GAM) revealed non-linear relationships between biodiversity intactness and key drivers: urban green space (UGS) exhibited threshold effects, with BII increasing significantly when vegetation indices exceeded critical levels (NDVI >0.40, EVI >0.20, VCF >60 %; R2 = 0.58–0.72, p < 0.001). Conversely, economic activity showed a strong negative association with BII (R2 = 0.87, p < 0.001), stabilizing at higher GDP densities (>40 million/km2). The findings contribute to a deeper understanding of the large-scale urban-rural gradient in biodiversity variation and may prove beneficial for the conservation of urban biodiversity.